Using the Extended Acceptance Model to Understand Continuance Intention of Dockless Bike-Sharing - Li, Xiadi; Lin, Hanchuan (Frontiers in Psychology, 2022)
Despite the fact that dockless bike-sharing (DBS) usage first experienced explosive growth, its continuous usage rate remains low. The ultimate success of a DBS service is more dependent on its continued usage rather than its initial adoption. Following the extended Technology Acceptance Model (TAM), this study aims to explore factors that influence DBS users’ continuance intention. The research framework was validated using a sample of 369 DBS users in China. The results show that perceived usefulness and perceived ease of use positively influence a user’s intention to continue using DBS. Both descriptive social norms and injunctive social norms are positively related to the continuance intention of DBS users. Moreover, environmental concern significantly affects a user’s continuance intention indirectly via perceived usefulness and perceived ease of use. Furthermore, the extended TAM has a stronger prediction ability than the original TAM in the context of DBS services.